Use of transient EPR spectroscopy of excited triplet state for the structural assignment of bisadducts of fullerene C60 - Pasimeni, Luigi; Hirsch, Andreas; Lamparth, Iris; Herzog, Andrea; Maggini, Michele; Prato, Maurizio; Scorrano, Gianfranco; et al. (Journal of the American Chemical Society, 1997)
Transient EPR spectroscopy has been applied to measure the spectra of excited triplet states in two series of fullerene bisadducts. Eight different bisadducts of C with bis(ethoxycarbonyl)methylene and five bis-N-methylpyrrolidines have been analyzed. The D and E parameters of electron dipolar interaction and the populations of the zero field triplet sublevels, accounting for spin polarization, have been determined by spectrum simulation. They appear peculiar for each bisadduct. It is shown that triplet EPR technique represents a useful spectroscopic tool that allows structural assignments to bisadducts of C.